One-step production and performance analysis of Phthalocyanine/CeO2/ TiO2 hybrid catalyst exhibiting photocatalytic properties under visible light - Buyuk, Esma; Gorduk, Semih; Avciata, Oguzhan; Avciata, Ulvi (ELSEVIER, 2026)
Water pollution causes serious environmental problems due to organic pollutants originating from the dye and textile industries. Therefore, pollutants must be removed using environmentally friendly and effective methods. This is also crucial for sustainable water management. In this context, CeO2, CeO2@TiO2 and NiPc@CeO2@TiO2 nanocomposites were synthesized and their photocatalytic activities were compared for photocatalysis. The characterization of these materials was performed using FT-IR, XRD, FE-SEM, EDS, XPS and UV-DRS techniques. Experiments were conducted for degradation of Methylene Blue (MB), an organic pollutant, under visible light using photocatalysis. The catalyst amount, dye concentration, and pH optimization were performed for the NiPc@CeO2@TiO2 composite. In the presence of 0.4 catalyst, in a 5 ppm MB solution, at pH value of 5, NiPc@CeO2@TiO2 composite exhibited 85.7 % photodegradation efficiency in 30 min. The study is innovative in terms of the synthesis of NiPc@CeO2@TiO2 ternary material containing phthalocyanine using the in-situ hydrothermal method for the first time and the performance of photocatalytic studies on MB.
Keywords: TiO2; CeO2; Phthalocyanine; Photocatalysis; Methylene Blue; Visible light; METHYLENE-BLUE; DEGRADATION; IRRADIATION; FABRICATION; Chemistry